Dietary Lactobacillus plantarum Relieves Nile Tilapia (Oreochromis niloticus) Juvenile From Oxidative Stress, Immunosuppression, and Inflammation Induced by Deltamethrin and Aeromonas hydrophila - Gewaily, Mahmoud S.; Shukry, Mustafa; Abdel-Kader, Marwa F.; Alkafafy, Mohamed; Farrag, Foad A.; Moustafa, Eman M.; Doan, Hien Van; Abd-Elghany, Mohamed F.; Abdelhamid, Ahmed F.; Eltanahy, Azhar; Dawood, Mahmoud A. O. (Frontiers in Marine Science, 2021)
Aeromonas hydrophila infection is one of the major diseases that cause inflammation and immunodepression in aquatic animals. Likewise, waterborne toxins are known for their negative impact on the immunity and antioxidant responses of aquatic organisms. In this study, Lactobacillus plantarum (LP20) was incorporated in Nile tilapia, Oreochromis niloticus, diets (50 mg/kg) to investigate its role in the antioxidant capacity, immunity, and anti-inflammation induced by deltamethrin (DLM) toxicity (96-h LC50 was 14.9 μg/L) and A. hydrophila (LD50, 2 × 108 CFU/ml). One hundred and twenty healthy fish with an initial weight of 28.21 ± 1.34 g were allotted in 12 glass aquaria (60 L) and divided randomly into four groups (triplicates, 10 fish per aquarium). The control fish neither received LP20 nor were exposed to DLM. The second group of fish was fed the control diet and subjected to DLM (DLM group). The third group of fish was provided with LP20 without DLM toxicity (LP20 group), and the fourth group of fish was fed LP20 and subjected to DLM (DLM + LP20 group). After 30 days, fish were intraperitoneally injected with A. hydrophila. Ten days post infection, the survival rate was lower in fish exposed to DLM than those exposed to LP20. Further, fish fed on LP20 had elevated serum total protein (sTP), albumin (ALB), globulin (GLB), phagocytic index (PI), phagocytic (PA), and lysozyme activities (LZM), but they had lower urea, uric acid bilirubin, creatinine, glucose, aspartate aminotransferase (AST), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) activities after 24 h, 48 h, and 1 week post A. hydrophila challenge. However, fish exposed to DLM had lower sTP, ALB, GLB and higher urea, uric acid, bilirubin, creatinine, glucose, ALT, AST, and ALP after 24 h, 48 h, and 1 week post A. hydrophila challenge. Markedly, after the A. hydrophila challenge, fish exposed to DLM + LP20 displayed upregulated levels of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) genes. The transcription of interferon gamma (IFN-γ), interleukin 12 (IL-12), and tumor necrosis factor alpha (TNF-α) was upregulated in DLM and DLM + LP20 groups. Fish exposed to DLM downregulated interleukin 8 (IL-8) gene expression after A. hydrophila challenge. Further, fish displayed upregulation of heat shock protein 70 (HSP70) gene expression after DLM toxicity. Besides, fish exposed to DLM toxicity and A. hydrophila infection had severe inflammatory features in the liver, spleen, gills, and intestine, while dietary LP20 relieved the inflammatory features. In summary, dietary LP20 relieves Nile tilapia from oxidative stress, immunosuppression, and inflammation induced by DLM and A. hydrophila infection.